2010
DOI: 10.1149/1.3387672
|View full text |Cite
|
Sign up to set email alerts
|

The Anodic Behavior of Planar and Porous Zinc Electrodes in Alkaline Electrolyte

Abstract: The electrochemical performance of planar and porous zinc electrodes in an actual Zn/MnO 2 battery using lithium hydroxide ͑LiOH͒ electrolyte has been investigated. A large discharge capacity of 220 mAh/g is delivered by porous zinc electrodes while planar electrodes only deliver 130 mAh/g. The porous anode improves the rate capability of the rechargeable alkaline battery while enhancing the utilization of the active material. Using scanning electron microscopy and IR spectroscopy, the surface morphology and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…This is reflected in increasing capacity during multiple cycling. The role of anodic zinc dissolution in aqueous LiOH solution during electrochemical discharge /charge cycles is reported by us earlier [27] which could inhibit the cycleability. To be suitable for practical applications, further work is needed to improve the specific capacity together with the cycle life of the olivine cathode mixed with all the three chelating agents (CA+ TEA+ PVP).…”
mentioning
confidence: 74%
“…This is reflected in increasing capacity during multiple cycling. The role of anodic zinc dissolution in aqueous LiOH solution during electrochemical discharge /charge cycles is reported by us earlier [27] which could inhibit the cycleability. To be suitable for practical applications, further work is needed to improve the specific capacity together with the cycle life of the olivine cathode mixed with all the three chelating agents (CA+ TEA+ PVP).…”
mentioning
confidence: 74%
“…Although it is not precisely an example of a zinc-air cell, Minakshi et al also showed that in the alkaline electrolyte LiOH, a porous anode electrode composed of zinc powder improves the rate capability and has a higher capacity in alkaline Zn-MnO 2 cells than that of a zinc planar electrode. [ 120 ] Recently, a study of porous electrodes with various shaped zinc particles, not just planar zinc electrodes, has also received attention. [ 121 ] Generally, when preparing a zinc anode with powder, mercury has been added to the zinc anode to give better electrical conductivity between the zinc particles and the current collectors.…”
Section: Anode: Zinc Electrodementioning
confidence: 99%
“…In a NiZn battery, higher zinc electrode surface area should lead to enhanced materials utilization and higher power density and reduce passivation at high discharge rates [20]. Porous electrode structure provides higher energy density due to short ion transport length and easy charge transfer reaction on electrode-electrolyte interface [39][40][41][42]. Therefore, high surface area for a zinc electrode is desirable as it should improve battery performance by providing enhanced path lengths for both electron and Zn ion transport, electrode/electrolyte contact area, and accommodation of the strain of the Zn ion insertion/extraction [43,44] [34,35].…”
Section: Charge/dischargementioning
confidence: 99%